A Large Area Organic Solar Module with Non‐Halogen Solvent Treatment, High Efficiency, and Decent Stability. Issue 7 (3rd February 2023) - Zhang, Shuchao; Chen, Hongbin; Wang, Peiran; Li, Shitong; Li, Zhixiang; Huang, Yuzhong; Liu, Jian; Yao, Zhaoyang; Li, Chenxi; Wan, Xiangjian; Chen, Yongsheng
Abstract : It is a challenge to fabricate organic solar modules with the combination of high efficiency, good stability, and green solvent treatment. To address the issue, active layer materials still play crucial roles. Herein, a non‐fullerene acceptor CH7 with the extended conjugation central unit and long‐branched side chains is reported for the fabrication of high‐performance large‐area modules. The long‐branched alkyl chains can ensure CH7 to have good solubility in non‐halogen solvent o‐xylene (OX). Meanwhile, the steric hindrance of long‐branched alkyl chains can suppress molecular excessive aggregation. The inverted structure prototype device based on PM6:CH7 and processed with OX showed a promising power conversion efficiency (PCE) of 17.49% mainly due to the favorable active layer morphology. Based on the small area device results, processed from OX, a 25.2 cm 2 module is fabricated and demonstrates a high PCE of 14.42% and good photo stability with maintaining 93% of its initial efficiency after 500 h continuous illumination. Moreover, the module also shows decent thermal stability, maintaining with 82% of its original efficiency after the thermal stress at 65 °C for 500 h. Abstract : An acceptor CH7 with the extended conjugation central unit and long‐branched side chains is reported and a 25.2 cm 2 organic solar module based on PM6:CH7 and processed from eco‐friendly solvent o‐xylene demonstrated high efficiency and decent stability.